Grain Legumes - Kumar Goyal, Aakash (IntechOpen, 2016)
Grain legumes are a main source of nitrogen-rich edible seeds and constitute a major source of dietary protein in the diets of human population especially for vegetarian diet. Legumes comprise the third largest family of flowering plants and provide important sources of food, fodder, oil, and fiber products. This book focuses on grain legumes production challenges, progress, and prospects. The book comprises a vast array of topics including diversity, biofortification, importance and antioxidant properties of pulse proteins, etc. This volume will serve as an excellent resource for students, researchers, and scientists interested and working in the area of sustainable crop production.